A New 200‐Year Spatial Reconstruction of West Antarctic Surface Mass Balance. Issue 10 (25th May 2019) - Wang, Yetang; Huai, Baojuan; Thomas, Elizabeth R.; van den Broeke, Michiel R.; van Wessem, J. Melchior; Schlosser, Elisabeth
Abstract: High‐spatial resolution surface mass balance (SMB) over the West Antarctic Ice Sheet (WAIS) spanning 1800–2010 is reconstructed by means of ice core records combined with the outputs of the European Centre for Medium‐Range Weather Forecasts "Interim" reanalysis (ERA‐Interim) and the latest polar version of the Regional Atmospheric Climate Model (RACMO2.3p2). The reconstruction reveals a significant negative trend (−1.9 ± 2.2 Gt/year·per decade) in the SMB over the entire WAIS during the nineteenth century, but a statistically significant positive trend of 5.4 ± 2.9 Gt/year·per decade between 1900 and 2010, in contrast to insignificant WAIS SMB changes during the twentieth century reported earlier. At regional scales, the Antarctic Peninsula and western WAIS show opposite SMB trends, with different signs in the nineteenth and twentieth centuries. The annual resolution reconstruction allows us to examine the relationships between SMB and large‐scale atmospheric oscillations. Although SMB over the Antarctic Peninsula and western WAIS correlates significantly with the Southern Annular Mode due to the influence of the Amundsen Sea Low, and El Niño/Southern Oscillation during 1800–2010, the significant correlations are temporally unstable, associated with the phase of Southern Annular Mode, El Niño/Southern Oscillation and the Pacific decadal oscillation. In addition, the two climate modes seem to contribute little to variability in SMB over the whole WAIS on decadal‐centennial time scales. This new reconstruction also serves to identify unreliable precipitation trends in ERA‐Interim and thus has potential for assessing the skill of other reanalyses or climate models to capture precipitation trends and variability. Key Points: A new reconstruction of spatially complete surface mass balance over the West Antarctic Ice Sheet during the past 200 years is presented West Antarctica experiences a significant negative SMB trend during the nineteenth century, but a significant positive trend during 1900–2010 The WAIS east‐west dipole SMB trends are associated with positive polarity of Southern Annular Mode (SAM) and dominant La Niña events